MENJAWAB TANTANGAN GEREJA KONTEMPORER DALAM SINERGI TEOLOGI MANAJEMEN DAN SOSIAL DI ERA MODERN - Manua, Englin (PT. Giat Konseling Nusantara, 2024)
This study explores the synergy between management theology and social theology in addressing the challenges faced by contemporary churches in the modern era. Using a descriptive qualitative approach and literature review, this research aims to provide an in-depth analysis of effective resource management strategies for churches while strengthening their role as agents of social transformation. The findings indicate that management theology can assist churches in enhancing service effectiveness through strategic planning, transparent resource management, and periodic program evaluations. Meanwhile, social theology offers an ethical foundation for churches to contribute to social justice issues, such as economic inequality and environmental crises. This study provides practical guidance for churches to navigate the dynamics of the times with a relevant and transformative interdisciplinary approach